Next Article in Journal
An Analytic Solution for the Dynamic Behavior of a Cantilever Beam with a Time-Dependent Spring-like Actuator
Next Article in Special Issue
Handling a Commensurate, Incommensurate, and Singular Fractional-Order Linear Time-Invariant System
Previous Article in Journal
Mathematical Modeling and Exact Optimizing of University Course Scheduling Considering Preferences of Professors
Previous Article in Special Issue
Efficient Technique for Solving (3+1)-D Fourth-Order Parabolic PDEs with Time-Fractional Derivatives

Font Type:
Arial Georgia Verdana
Font Size:
Aa Aa Aa
Line Spacing:
Column Width:
Background:
Article

# A New Hardy–Hilbert-Type Integral Inequality Involving One Multiple Upper Limit Function and One Derivative Function of Higher Order

1
Department of Mathematics, Guangdong University of Education, Guangzhou 510303, China
2
Department of Mathematics and Engineering Sciences, Hellenic Military Academy, 16673 Vari Attikis, Greece
3
Institute for Advanced Study, Program in Interdisciplinary Studies, 1 Einstein Dr, Princeton, NJ 08540, USA
*
Author to whom correspondence should be addressed.
Axioms 2023, 12(5), 499; https://doi.org/10.3390/axioms12050499
Original submission received: 8 April 2023 / Revised: 11 May 2023 / Accepted: 16 May 2023 / Published: 19 May 2023
(This article belongs to the Special Issue Fractional Calculus - Theory and Applications II)

## Abstract

:
Using weight functions and parameters, as well as applying real analytic techniques, we derive a new Hardy–Hilbert-type integral inequality with the homogeneous kernel $1 ( x + y ) λ + n$ involving one multiple upper limit function and one derivative function of higher order. Certain equivalent statements of the optimal constant factor related to some parameters are considered. A few particular inequalities and the case of reverses are also provided.
MSC:
26D15; 47A05

## 1. Introduction

Assuming that $p > 1 , 1 p + 1 q = 1 , a m , b n ≥ 0 ,$
$0 < ∑ m = 1 ∞ a m p < ∞$
and
$0 < ∑ n = 1 ∞ b n q < ∞ ,$
the following Hardy–Hilbert inequality with the optimal constant factor $π / sin ( π p )$ has been proven (cf. , Theorem 315):
$∑ n = 1 ∞ ∑ m = 1 ∞ a m b n m + n < π sin ( π / p ) ∑ m = 1 ∞ a m p 1 p ∑ n = 1 ∞ b n q 1 q .$
If $f ( x ) , g ( y ) ≥ 0 ,$
$0 < ∫ 0 ∞ f ( x ) d x < ∞$
and
$0 < ∫ 0 ∞ g ( y ) d y < ∞ ,$
then we still have the following integral analogue of (1) known as Hardy–Hilbert integral inequality (cf. , Theorem 316):
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) x + y d x d y < π sin ( π / p ) ∫ 0 ∞ f p ( x ) d x 1 p ∫ 0 ∞ g q ( y ) d y 1 q ,$
where the identical constant factor $π / sin ( π p )$ remains optimal. Inequalities (1) and (2) have proven to be essential in various applications of mathematical analysis (cf. [2,3,4,5,6,7,8,9,10,11,12,13]).
In 2006, applying the Euler–Maclaurin summation formula, Krnic et al.  established an extension of (1) with the kernel $1 ( m + n ) λ ( 0 < λ ≤ 4 )$. Making use of the result of , in 2019, Adiyasuren et al.  considered an extension of (1), which involved two partial sums, and subsequently, in 2020, Mo et al.  proved an extension of (2), which involved two upper-limit functions. In 2016–2017, Hong et al. [17,18] presented several equivalent statements of the extensions of (1) and (2) with the best possible constant factors and multi-parameters. Some similar results were established in [19,20,21,22,23,24,25,26,27].
In the present paper, following the methods of [15,17], using weight functions and parameters, as well as applying real analytic techniques, we prove a new Hardy–Hilbert-type integral inequality with the kernel $1 ( x + y ) λ + n$ involving one multiple upper limit function and one derivative function of higher order. Equivalent statements of the best possible constant factor related to the parameters are considered. Some particular inequalities and the case of reverses are obtained. The lemmas and theorems provide an extensive account of this type of inequalities.

## 2. Some Lemmas

In what follows, we suppose that $p > 0$ $( p ≠ 1 ) , 1 p + 1 q = 1$ $, m , n ∈ N = { 1 , 2 , ⋯ } ,$ $λ > − min { m , n } ,$ $− m < λ 1 < λ ,$ $0 < λ 2 < λ + m ,$ $λ ^ 1 : = λ − λ 2 p + λ 1 q ,$ $λ ^ 2 : = λ − λ 1 q + λ 2 p$ and the following
Assumption (I):
For $F 0 ( x ) : = f ( x )$, being a non-negative continuous function, except for finitely many points in $R + = ( 0 , ∞ ) ,$ satisfying
$f ( x ) = o ( e t x ) ( t > 0 ; x → ∞ ) ,$
$F k ( x ) : = ∫ 0 x F k − 1 ( x ) d x ( k = 1 , ⋯ , m ) ,$
$g ( n ) ( y )$ is a non-negative continuous function, except for finite points in $R + ,$ satisfying
$g ( n ) ( y ) = o ( e t y ) ( t > 0 ; y → ∞ ) ,$
$g ( 0 ) ( y ) = g ( y ) ,$
$g ( j − 1 ) ( y )$ is a non-negative differentiable function in $R +$ with
$g ( j − 1 ) ( 0 + ) = 0 ( j = 1 , ⋯ , n ) .$
We also assume that
$0 < ∫ 0 ∞ x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) d x < ∞ and 0 < ∫ 0 ∞ y q ( 1 − λ ^ 2 ) − 1 ( g ( n ) ( y ) ) q d y < ∞ .$
Note: According to Assumption (I), since $f ( x ) ≥ 0 ,$ $F k ( x )$ is increasing and $F k ( ∞ ) = ∞$ or constant. If there exists a last constant $k 0 ≤ k$ such that $F k 0 ( ∞ ) =$ constant, then
$lim x → ∞ F k ( x ) e t x = ⋯ = 1 t k − k 0 lim x → ∞ F k 0 ( x ) e t x = 0 ;$
otherwise, we still have
$lim x → ∞ F k ( x ) e t x = ⋯ = 1 t k lim x → ∞ f ( x ) e t x = 0 ,$
namely,
$F k ( x ) = o ( e t x ) ( t > 0 ; x → ∞ ) ( k = 1 , ⋯ , m ) .$
In the same way, we still can show that
$g ( j − 1 ) ( y ) = o ( e t y ) ( t > 0 ; y → ∞ ) ( j = 1 , ⋯ , n ) .$
We define the gamma function as follows:
$Γ ( α ) : = ∫ 0 ∞ e − t t α − 1 d t ( α > 0 ) ,$
satisfying $Γ ( α + 1 ) = α Γ ( α ) ( α > 0 )$, and define the following beta function (cf. ):
$B ( u , v ) : = ∫ 0 ∞ t u − 1 ( 1 + t ) u + v d t = Γ ( u ) Γ ( v ) Γ ( u + v ) ( u , v > 0 ) .$
According to (3), for $λ , x , y > 0 ,$ we still have the following formula related to the gamma function:
$1 ( x + y ) λ = 1 Γ ( λ ) ∫ 0 ∞ e − ( x + y ) t t λ − 1 d t .$
Lemma 1.
For $t > 0 , m , n ∈ N ,$ we have the following expressions:
$∫ 0 ∞ e − t x f ( x ) d x = t m ∫ 0 ∞ e − t x F m ( x ) d x ,$
$∫ 0 ∞ e − t y g ( y ) d y = t − n ∫ 0 ∞ e − t y g ( n ) ( y ) d y .$
Proof.
According to Assumption (I), for $k = 1 , ⋯ , m ,$ we get that $e − t x F k ( x ) | 0 ∞ = 0$, then integration by parts,
$∫ 0 ∞ e − t x F k − 1 ( x ) d x = ∫ 0 ∞ e − t x d F k ( x ) = e − t x F k ( x ) | 0 ∞ − ∫ 0 ∞ F k ( x ) d e − t x = t ∫ 0 ∞ e − t x F k ( x ) ( x ) d x .$
Substituting $k = 1 , … , m$ in the above expression, by simplification, we obtain (6).
According to Assumption (I), for $j = 1 , ⋯ , n ,$ we get that $e − t y g ( j − 1 ) ( y ) | 0 ∞ = 0 ,$ and
$∫ 0 ∞ e − t y g ( j ) ( y ) d y = ∫ 0 ∞ e − t y d g ( j − 1 ) ( y ) = e − t y g ( j − 1 ) ( y ) | 0 ∞ − ∫ 0 ∞ g ( j − 1 ) ( y ) d e − t y = t ∫ 0 ∞ e − t y g ( j − 1 ) ( y ) d y .$
Substituting $j = 1 , ⋯ , n$ in the above expression, we obtain (7).
This completes the proof of the lemma.    □
Note: (6) (resp. (7)) is naturally the value for $m = 0$ (resp. $n = 0 ) .$
Lemma 2.
For $0 < s 1 , s 2 < s ,$ define the following weight functions:
$ω s ( s 2 , x ) : = x s − s 2 ∫ 0 ∞ t s 2 − 1 ( x + t ) s d t ( x ∈ R + ) ,$
$ω s ( s 1 , y ) : = y s − s 1 ∫ 0 ∞ t s 1 − 1 ( x + t ) s d t ( y ∈ R + ) .$
We have the following expressions:
$ω s ( s 2 , x ) : = B ( s 2 , s − s 2 ) ( x ∈ R + ) ,$
$ω s ( s 1 , y ) : = B ( s 1 , s − s 1 ) ( y ∈ R + ) .$
Proof.
Setting $u = t x$, we derive
$ω s ( s 2 , x ) = x s − s 2 ∫ 0 ∞ ( u x ) s 2 − 1 ( x + u x ) s x d u = ∫ 0 ∞ u s 2 − 1 d u ( 1 + u ) s = B ( s 2 , s − s 2 ) ,$
namely, (10) follows. In the same way, we obtain (11).
This completes the proof of the lemma.    □
Lemma 3.
Suppose that $λ > − m , − m < λ 1 < λ , 0 < λ 2 < λ + m .$
(i)
For $p > 1 ,$ we have the following extended Hardy–Hilbert integral inequality:
$I λ + m : = ∫ 0 ∞ ∫ 0 ∞ F m ( x ) g ( n ) ( y ) ( x + y ) λ + m d x d y < B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) × ∫ 0 ∞ x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ ^ 2 ) − 1 ( g ( n ) ( y ) ) q d y 1 q ;$
(ii)
for $0 < p < 1 ,$ we have the reverse of (13).
Proof.
(i) By Hölder’s inequality (cf. ), we obtain
$I λ + m = ∫ 0 ∞ ∫ 0 ∞ 1 ( x + y ) λ + m y ( λ 2 − 1 ) / p x ( λ 1 + m − 1 ) / q F m ( x ) × x ( λ 1 + m − 1 ) / q y ( λ 2 − 1 ) / p g ( n ) ( y ) d x d y ≤ ∫ 0 ∞ ∫ 0 ∞ 1 ( x + y ) λ + m y λ 2 − 1 x ( λ 1 + m − 1 ) ( p − 1 ) d y F m p ( x ) d x 1 p × ∫ 0 ∞ ∫ 0 ∞ 1 ( x + y ) λ + m x λ 1 + m − 1 y ( λ 2 − 1 ) ( q − 1 ) d x ( g ( n ) ( y ) ) q d y 1 q = ∫ 0 ∞ ω λ + m ( λ 2 , x ) x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) d x 1 p × ∫ 0 ∞ ω λ + m ( λ 1 + m , y ) y q ( 1 − λ ^ 2 ) − 1 ( g ( n ) ( y ) ) q d y 1 q .$
If (14) retains the form of equality, then, there exist constants A and B such that they are not both zero, satisfying
$A y λ 2 − 1 x ( λ 1 + m − 1 ) ( p − 1 ) F m p ( x ) = B x λ 1 + m − 1 y ( λ 2 − 1 ) ( q − 1 ) ( g ( n ) ( y ) ) q a . e . in R + 2 .$
Assuming that $A ≠ 0$, for fixed $a , e ,$ $y ∈ R + ,$ we have
$x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) = [ B A y q ( 1 − λ ^ 2 ) ( g ( n ) ( y ) ) q ] x − 1 − ( λ − λ 1 − λ 2 ) a . e . in R + .$
Since for any $a : = λ − λ 1 − λ 2 ∈ R$, $∫ 0 ∞ x − 1 − a d x = ∞$, the above expression contradicts the fact that
$0 < ∫ 0 ∞ x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) d x < ∞ .$
Therefore, by (10) and (11), setting $s = λ + m$ $( > 0 ) , s 1 = λ 1 + m$ $( ∈ ( 0 , λ + m ) ) ,$ $s 2 = λ 2$ $( ∈ ( 0 , λ + m ) )$, in view of (14), we have (13).
(ii) Similarly, according to the reverse Hölder inequality, we obtain the reverse of (13).
This completes the proof of the lemma.    □

## 3. Main Results

Theorem 1.
Suppose that $λ > − min { m , n } ,$ $− m < λ 1 < λ , 0 < λ 2 < λ + m .$
(i)
For $p > 1 ,$ we have the following Hardy–Hilbert-type integral inequality involving one multiple upper limit function and one derivative function of higher order:
$I : = ∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + n d x d y < Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) × ∫ 0 ∞ x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ ^ 2 ) − 1 ( g ( n ) ( y ) ) q d y 1 q .$
(ii)
For $0 < p < 1 ,$ we obtain the reverse of (14).
In particular, for $λ 1 + λ 2 = λ$ $( 0 < λ 1 , λ 2 < λ ) ,$ we reduce (14) to the following:
$I = ∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + n d x d y < Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 ) × ∫ 0 ∞ x p ( 1 − λ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ 2 ) − 1 ( g ( n ) ( y ) ) q d y 1 q ,$
where the constant factor $Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 )$ is the best possible.
Proof.
(i) In view of (6), (7) and Fubini’s theorem (cf. ), we obtain
$I = 1 Γ ( λ + n ) ∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ∫ 0 ∞ t λ + n − 1 e − ( x + y ) t d t d x d y = 1 Γ ( λ + n ) ∫ 0 ∞ t λ + n − 1 ∫ 0 ∞ e − x t f ( x ) d x ∫ 0 ∞ g ( y ) e − y t d y d t = 1 Γ ( λ + n ) ∫ 0 ∞ t λ + n − 1 t m ∫ 0 ∞ e − x t F m ( x ) d x t − n ∫ 0 ∞ g ( n ) ( y ) e − y t d y d t = 1 Γ ( λ + n ) ∫ 0 ∞ ∫ 0 ∞ F m ( x ) g ( n ) ( y ) ∫ 0 ∞ t λ + m − 1 e − ( x + y ) t d t d x d y = Γ ( λ + m ) Γ ( λ + n ) ∫ 0 ∞ ∫ 0 ∞ F m ( x ) g ( n ) ( y ) ( x + y ) λ + m d x d y = Γ ( λ + m ) I λ + m Γ ( λ + n ) .$
Then, according to (13), we obtain (14).
(ii) According to (17) and the reverse of (13), we derive the reverse of (14).
For $λ 1 + λ 2 = λ$ $( 0 < λ 1 , λ 2 < λ )$ in (14), we deduce (15).
For any $0 < ε < min { p λ 1 , q λ 2 } ,$ we set the following functions:
$F ˜ 0 ( x ) = f ˜ ( x ) : = 0 , 0 < x < 1 , x λ 1 − ε p − 1 , x ≥ 1 , F ˜ k ( x ) = ∫ 0 x ( ∫ 0 t k − 1 ⋯ ∫ 0 t 2 f ˜ ( t 1 ) d t 1 ⋯ d t k − 1 ) d t k ( k = 1 , ⋯ , m ) ,$
and then $F ˜ m ( x ) = 0 , 0 < x < 1 ,$
$F ˜ m ( x ) = ∫ 1 x ( ∫ 1 t m − 1 ⋯ ∫ 1 t 2 t 1 λ 1 − ε p − 1 d t 1 ⋯ d t m − 1 ) d t m = [ ∏ i = 0 m − 1 ( λ 1 − ε p + i ) ] − 1 ( x λ 1 − ε p + m − 1 − O 1 ( x m − 1 ) ) ≤ [ ∏ i = 0 m − 1 ( λ 1 − ε p + i ) ] − 1 x λ 1 − ε p + m − 1 ( x ≥ 1 ) ,$
where $O 1 ( x m − 1 )$ $( x ≥ 1 )$ is a positive polynomial of $( m − 1 )$-degree. We also set
$g ˜ ( n ) ( y ) = 0 , 0 < y ≤ 1 , ∏ i = 0 n − 1 ( λ 2 + j − ε q ) y λ 2 − ε q − 1 , y > 1 , g ˜ ( l ) ( y ) = ∏ j = 0 l − 1 ( λ 2 + j − ε q ) ∫ 0 y ( ∫ 0 t n − l − 1 ⋯ ∫ 0 t 2 g ˜ ( n ) ( t 1 ) d t 1 ⋯ d t n − l − 1 ) d t n − l ( l = 1 , ⋯ , n ) ,$
and $g ˜ ( y ) = 0$ $( 0 < y ≤ 1 ) ,$
$g ˜ ( y ) = ∏ j = 0 n − 1 ( λ 2 + j − ε q ) ∫ 1 y ( ∫ 1 t n − 1 ⋯ ∫ 1 t 2 t 1 λ 2 − ε q − 1 d t 1 ⋯ d t n − 1 ) d t n = y λ 2 − ε q + n − 1 − O 2 ( y n − 1 ) ≤ y λ 2 − ε q + n − 1 ( y > 1 ) ,$
where $O 2 ( y n − 1 )$ $( y > 1 )$ is a positive polynomial of $n − 1$-degree.
We observe that $F ˜ k ( x )$ $( k = 0 , ⋯ , m )$ and $g ˜ ( l ) ( y )$ $( l = 0 , ⋯ , n )$ all satisfy Assumption (I) on $F k , g ( l )$.
If there exists a positive constant
$M ≤ Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 )$
such that (15) is valid when we replace $Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 )$ with M, then, in particular, since
$J ˜ : = ∫ 0 ∞ x p ( 1 − λ 1 − m ) − 1 F ˜ m p ( x ) ) d x 1 p ∫ 0 ∞ y q ( 1 − λ 2 ) − 1 ( g ˜ ( n ) ( y ) ) q d y 1 q ≤ [ ∏ i = 0 m − 1 ( λ 1 + i − ε p ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j − ε q ) ∫ 1 ∞ x − ε − 1 d x = 1 ε [ ∏ i = 0 m − 1 ( λ 1 + i − ε p ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j − ε q ) ,$
we have
$I ˜ : = ∫ 0 ∞ ∫ 0 ∞ f ˜ ( x ) g ˜ ( y ) ( x + y ) λ + n d x d y < M J ˜ = M ε [ ∏ i = 0 m − 1 ( λ 1 + i − ε p ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j − ε q ) .$
In view of Fubini’s theorem (cf. ), it follows that
$I ˜ = ∫ 1 ∞ ∫ 1 ∞ y λ 2 + n − ε q − 1 − O 2 ( y n − 1 ) ( x + y ) λ + n d y x λ 1 − ε p − 1 d x = I 0 − I 1 ,$
where
$I 0 = ∫ 1 ∞ ∫ 1 ∞ y λ 2 + n − ε q − 1 ( x + y ) λ + n d y x λ 1 + m − ε p − 1 d x = ∫ 1 ∞ x − ε − 1 ∫ 1 x ∞ u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u d x = ∫ 1 ∞ x − ε − 1 ∫ 1 x 1 u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u d x + 1 ε ∫ 1 ∞ u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u = ∫ 0 1 ∫ 1 u 1 x − ε − 1 d x u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u + 1 ε ∫ 1 ∞ u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u = 1 ε ∫ 0 1 u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u + ∫ 1 ∞ u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u ,$
$0 < I 1 : = ∫ 1 ∞ ∫ 1 ∞ O 2 ( y n − 1 ) ( x + y ) λ + n d y x λ 1 − ε p − 1 d x = ∫ 1 ∞ ∫ 1 ∞ O 2 ( y n − 1 ) ( x + y ) ( λ 2 / 2 ) + n d y x λ 1 − ε p − 1 ( x + y ) λ 1 + ( λ 2 / 2 ) d x ≤ ∫ 1 ∞ ∫ 1 ∞ O 2 ( y n − 1 ) y ( λ 2 / 2 ) + n d y x λ 1 − ε p − 1 x λ 1 + ( λ 2 / 2 ) d x = ∫ 1 ∞ x − λ 2 2 − ε p − 1 d x ∫ 1 ∞ O ( y − λ 2 2 − 1 ) d y ≤ M 1 < ∞ .$
According to the above results, it follows that
$∫ 0 1 u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u + ∫ 1 ∞ u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u − ε I 1 = ε I ˜ < M [ ∏ i = 0 m − 1 ( λ 1 + i − ε p ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j − ε q ) .$
Letting $ε → 0 +$ in the above inequality, in view of the continuity of the beta function, we obtain
$B ( λ 1 , λ 2 + n ) ≤ M [ ∏ i = 0 m − 1 ( λ 1 + i ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j ) ,$
namely,
$Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 ) = B ( λ 1 , λ 2 + n ) ∏ i = 0 m − 1 ( λ 1 + i ) [ ∏ j = 0 n − 1 ( λ 2 + j ) ] − 1 ≤ M$
and then
$M = Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 )$
is the best possible constant factor of (15).
This completes the proof of the theorem.    □
Remark 1.
For $λ ^ 1 = λ − λ 2 p + λ 1 q ,$ $λ ^ 2 = λ − λ 1 q + λ 2 p ,$ it follows that $λ ^ 1 +$ $λ ^ 2 = λ .$ We find $0 < λ ^ 1 < λ p + λ q = λ$, then $0 < λ ^ 2 = λ − λ ^ 1 < λ$. According to Hölder’s inequality (cf. ), it follows that
$0 < B ( λ ^ 1 + m , λ ^ 2 ) = ∫ 0 ∞ u λ + m − λ 2 p + λ 1 + m q − 1 ( 1 + u ) λ + m d u = ∫ 0 ∞ 1 ( 1 + u ) λ + m u λ + m − λ 2 − 1 p u λ 1 + m − 1 q d u ≤ ∫ 0 ∞ u λ + m − λ 2 − 1 ( 1 + u ) λ + m d u 1 p ∫ 0 ∞ u λ 1 + m − 1 ( 1 + u ) λ + m d u 1 q = B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) < ∞ .$
Theorem 2.
For $p > 1 ,$ if the constant factor
$Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
in (14) is the best possible, then for $0 < λ 1 , λ 2 < λ ,$ we have $λ 1 + λ 2 = λ$.
Proof.
According to (15) (for $λ i = λ ^ i ( i = 1 , 2 )$), since
$Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
is the best possible constant factor in (14), we have
$Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) ≤ Γ ( λ + m ) Γ ( λ + n ) B ( λ ^ 1 + m , λ ^ 2 ) ( ∈ R + ) ,$
namely
$B ( λ ^ 1 + m , λ ^ 2 ) ≥ B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) .$
It follows that (18) retains the form of equality.
We observe that (18) retains the form of equality if and only if there exist constants A and B such that they are not both zero and $A u λ + m − λ 2 − 1 = B u λ 1 + m − 1$ $a . e .$ in $R +$ (cf. ). Assuming that $A ≠ 0$, it follows that $u λ − λ 2 − λ 1 = B / A$ $a . e .$ in $R +$, namely, $λ − λ 2 − λ 1 = 0$. Hence, we have $λ 1 + λ 2 = λ$.
This completes the proof of the theorem.    □
Theorem 3.
The following statements ((i), (ii), (iii) and (iv)) are equivalent:
(i)
Both
$B 1 p ( λ 2 , λ + m + − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
and
$B λ − λ 2 p + λ 1 q + m , λ − λ 1 q + λ 2 p$
are independent of $p , q$;
(ii
$B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) = B ( λ − λ 2 p + λ 1 q + m , λ − λ 1 q + λ 2 p )$;
(iii)
For $0 < λ 1 , λ 2 < λ ,$ we have $λ 1 + λ 2 = λ$;
(iv)
The constant factor
$Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
is the best possible in (14).
Proof.
$( i ) ⇒ ( i i )$. In view of the continuity of the beta function, we derive
$B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) = lim p → ∞ lim q → 1 + B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) = B ( λ 1 + m , λ − λ 1 ) , B λ − λ 2 p + λ 1 q + m , λ − λ 1 q + λ 2 p = lim p → ∞ lim q → 1 + B λ − λ 2 p + λ 1 q + m , λ − λ 1 q + λ 2 p = B λ 1 + m , λ − λ 1 .$
Hence, we have
$B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) = B λ − λ 2 p + λ 1 q + m , λ − λ 1 q + λ 2 p .$
$( i i ) ⇒ ( i i i )$. In view of
$B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) = B ( λ ^ 1 , λ ^ 2 ) ,$
(17) retains the form of equality. In view of the proof of Theorem 2, we have
$λ 1 + λ 2 = λ .$
$( i i i ) ⇒ ( i v )$. If $λ 1 + λ 2 = λ$$( 0 < λ 1 , λ 2 < λ )$, then according to Theorem 1, the constant factor
$Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
in (14) is the best possible.
$( i v ) ⇒ ( i )$. According to Theorem 2, we have $λ 1 + λ 2 = λ$; then,
$B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) = B ( λ 1 + m , λ 2 ) , B λ − λ 2 p + λ 1 q + m , λ − λ 1 q + λ 2 p = B ( λ 1 + m , λ 2 ) ,$
both of which are independent of $p , q$.
Hence, statements (i), (ii), (iii) and (iv) are equivalent.
This completes the proof of the theorem.    □
For $n = m ,$ we have:
Corollary 1.
For $p > 1 ,$ we have the following Hardy–Hilbert-type integral inequality involving one multiple upper limit function and one derivative function of m-order:
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + m d x d y < B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) × ∫ 0 ∞ x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ ^ 2 ) − 1 ( g ( m ) ( y ) ) q d y 1 q .$
Moreover, for $0 < λ 1 , λ 2 < λ ,$ the constant factor
$B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
in (19) is the best possible if and only if $λ 1 + λ 2 = λ .$ For
$λ 1 + λ 2 = λ ( 0 < λ 1 , λ 2 < λ ) ,$
we reduce (19) to the following:
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + m d x d y < B ( λ 1 + m , λ 2 ) × ∫ 0 ∞ x p ( 1 − λ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ 2 ) − 1 ( g ( m ) ( y ) ) q d y 1 q ,$
where the constant factor $B ( λ 1 + m , λ 2 )$ is the best possible factor.
Remark 2.
(i) For $λ 1 + λ 2 = λ$ in (13), we have
$I λ + m = ∫ 0 ∞ ∫ 0 ∞ F m ( x ) g ( n ) ( y ) ( x + y ) λ + m d x d y < B ( λ 1 + m , λ 2 ) × ∫ 0 ∞ x p ( 1 − λ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ 2 ) − 1 ( g ( n ) ( y ) ) q d y 1 q .$
We confirm that the constant factor $B ( λ 1 + m , λ 2 )$ in (20) is the best possible. Otherwise, we would reach a contradiction according to (17) (for $λ 1 + λ 2 = λ$) that the constant factor in (15) is not the best possible.
(ii) In view of the note of Lemma 1, Theorem 1, Theorem 2 and Theorem 3 are valid for $m = 0$ or $n = 0 .$ For $m = n = 0 , λ = 1 , λ 1 = 1 q , λ 2 = 1 p ,$ both (15) and (20) reduce to (2).
Remark 3.
(i) For $λ = 1 , λ 1 = 1 q , λ 2 = 1 p$ in (15), we have
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) 1 + n d x d y < π n ! sin ( π p ) ∏ i = 0 m − 1 ( 1 q + i ) × ∫ 0 ∞ x − p m F m p ( x ) d x 1 p ∫ 0 ∞ ( g ( n ) ( y ) ) q d y 1 q ;$
(ii) For $λ = 1 , λ 1 = 1 p , λ 2 = 1 q$ in (15), we have the dual form of (21) as follows:
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) 1 + n d x d y < π n ! sin ( π p ) ∏ i = 0 m − 1 ( 1 p + i ) × ∫ 0 ∞ x p ( 1 − m ) − 2 F m p ( x ) d x 1 p ∫ 0 ∞ y p − 2 ( g ( n ) ( y ) ) q d y 1 q ;$
(iii) For $p = q = 2 ,$ both (15) and (21) reduce to
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) 1 + n d x d y < π ( 2 m − 1 ) ! ! n ! 2 m ∫ 0 ∞ x − 2 m F m 2 ( x ) d x ∫ 0 ∞ ( g ( n ) ( y ) ) 2 d y 1 2 .$
The constant factors in the above inequalities are all the best possible.

## 4. The Reverses

According to Lemma 3 and Theorem 1 (ii), we have:
Theorem 4.
For $0 < p < 1$ $( q < 0 ) ,$ we have the following reverse Hardy–Hilbert-type integral inequality involving one multiple upper limit function and one derivative function of higher order:
$I = ∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + n d x d y > Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) × ∫ 0 ∞ x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ ^ 2 ) − 1 ( g ( n ) ( y ) ) q d y 1 q .$
In particular, for $λ 1 + λ 2 = λ$ $( 0 < λ 1 , λ 2 < λ ) ,$ we reduce (24) to the following:
$I = ∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + n d x d y > Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 ) × ∫ 0 ∞ x p ( 1 − λ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ 2 ) − 1 ( g ( n ) ( y ) ) q d y 1 q ,$
where the constant factor
$Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 )$
is the best possible.
Proof.
We only prove that the constant factor $Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 )$ in (25) is the best possible.
For any $0 < ε < λ 1 min { p , | q | } ,$ we consider the functions $F ˜ k ( x )$ $( k = 0 , ⋯ , m )$ and $g ˜ ( n − l ) ( y )$ $( l = 0 , ⋯ , n )$ as in Theorem 1. If there exists a positive constant
$M ≥ Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 ) ,$
such that (25) is valid when we replace $Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 )$ with M, then in particular, since
$J ˜ : = ∫ 0 ∞ x p ( 1 − λ 1 − m ) − 1 F ˜ m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ 2 ) − 1 ( g ˜ ( n ) ( y ) ) p d y 1 q = ∫ 1 ∞ x − ε − 1 d x − ∫ 1 ∞ O 1 ( x − p λ 1 − 1 ) d x 1 p ∫ 1 ∞ y − ε − 1 d y 1 q = 1 ε [ ∏ i = 0 m − 1 ( λ 1 + i − ε p ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j − ε q ) ( 1 − ε O ( 1 ) ) 1 p ,$
we have
$I ˜ : = ∫ 0 ∞ ∫ 0 ∞ f ˜ ( x ) g ˜ ( y ) ( x + y ) λ d x d y > M J ˜ = M ε [ ∏ i = 0 m − 1 ( λ 1 + i − ε p ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j − ε q ) ( 1 − ε O ( 1 ) ) 1 p .$
In view of the proof of the results of Theorem 1, it follows that
$I ˜ = ∫ 1 ∞ ∫ 1 ∞ y λ 2 + n − ε q − 1 − O 2 ( y n − 1 ) ( x + y ) λ + n d y x λ 1 − ε p − 1 d x = I 0 − I 1 ,$
where
$I 0 = ∫ 1 ∞ ∫ 1 ∞ y λ 2 + n − ε q − 1 ( x + y ) λ + n d y x λ 1 − ε p − 1 d x = 1 ε ∫ 0 1 u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u + ∫ 1 ∞ u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u .$
$0 < I 1 = ∫ 1 ∞ ∫ 1 ∞ O 2 ( y n − 1 ) ( x + y ) λ + n d y x λ 1 − ε p − 1 d x ≤ M 2 < ∞ ,$
According to the above results, it follows that
$∫ 0 1 u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u + ∫ 1 ∞ u λ 2 + n − ε q − 1 ( 1 + u ) λ + n d u − ε I 1 = ε I ˜ > M [ ∏ i = 0 m − 1 ( λ 1 + i − ε p ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j − ε q ) ( 1 − ε O ( 1 ) ) 1 p .$
Letting $ε → 0 +$ in the above inequality, in view of the continuity of the beta function, we obtain
$B ( λ 1 , λ 2 + n ) ≥ M [ ∏ i = 0 m − 1 ( λ 1 + i ) ] − 1 ∏ j = 0 n − 1 ( λ 2 + j ) ,$
namely
$Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 ) = B ( λ 1 , λ 2 + n ) ∏ i = 0 m − 1 ( λ 1 + i ) [ ∏ j = 0 n − 1 ( λ 2 + j ) ] − 1 ≥ M$
and then, $M = Γ ( λ + m ) Γ ( λ + n ) B ( λ 1 + m , λ 2 )$ is the best possible constant factor of (25).
This completes the proof of the theorem.    □
Remark 4.
For
$λ ^ 1 = λ − λ 2 p + λ 1 q = λ − λ 1 − λ 2 p + λ 1 ,$
$λ ^ 2 = λ − λ 1 q + λ 2 p = λ − λ 1 − λ 2 q + λ 2 ,$
it follows that $λ ^ 1 +$ $λ ^ 2 = λ .$ We find that for
$− p λ 1 < λ − λ 1 − λ 2 < p ( λ − λ 1 ) ,$
$0 < λ ^ 1 < λ ;$
then,
$0 < λ ^ 2 = λ − λ ^ 1 < λ .$
According to the reverse Hölder inequality (cf. ), we obtain
$∞ > B ( λ ^ 1 + m , λ ^ 2 ) = ∫ 0 ∞ u λ + m − λ 2 p + λ 1 + m q − 1 ( 1 + u ) λ + m d u = ∫ 0 ∞ 1 ( 1 + u ) λ + m u λ + m − λ 2 − 1 p u λ 1 + m − 1 q d u ≥ ∫ 0 ∞ u λ + m − λ 2 − 1 ( 1 + u ) λ + m d u 1 p ∫ 0 ∞ u λ 1 + m − 1 ( 1 + u ) λ + m d u 1 q = B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) > 0 .$
Theorem 5.
For $0 < p < 1 ,$ $0 < λ 1 , λ 2 < λ ,$ if the constant factor
$Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
in (24) is the best possible, then for $− p λ 1 < λ − λ 1 − λ 2 < p ( λ − λ 1 ) ,$ we have $λ 1 + λ 2 = λ$.
Proof.
For $− p λ 1 < λ − λ 1 − λ 2 < p ( λ − λ 1 ) ,$ by (25) (for $λ i = λ ^ i ( i = 1 , 2 )$), since
$Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
is the best possible constant factor in (24), we have
$Γ ( λ + m ) Γ ( λ + n ) B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) ≥ Γ ( λ + m ) Γ ( λ + n ) B ( λ ^ 1 + m , λ ^ 2 ) ( ∈ R + ) ,$
namely,
$B ( λ ^ 1 + m , λ ^ 2 ) ≤ B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) .$
It follows that (27) retains the form of equality.
We observe that (27) retains the form of equality if and only if there exist constants A and B such that they are not both zero and $A u λ + m − λ 2 − 1 = B u λ 1 + m − 1$ $a . e .$ in $R +$ (cf. ). Assuming that $A ≠ 0$, it follows that $u λ − λ 2 − λ 1 = B / A$ $a . e .$ in $R +$, namely $λ − λ 2 − λ 1 = 0$; then, $λ 1 + λ 2 = λ$.
This completes the proof of the theorem.    □
For $n = m ,$ we have:
Corollary 2.
For $0 < p < 1 ,$ we have the following reverse Hardy–Hilbert-type integral inequality involving one multiple upper limit function and one derivative function of m-order:
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + m d x d y > B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 ) × ∫ 0 ∞ x p ( 1 − λ ^ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ ^ 2 ) − 1 ( g ( m ) ( y ) ) q d y 1 q .$
Moreover, if $0 < λ 1 , λ 2 < λ ,$ the constant factor
$B 1 p ( λ 2 , λ + m − λ 2 ) B 1 q ( λ 1 + m , λ − λ 1 )$
in (28) is the best possible, then for
$− p λ 1 < λ − λ 1 − λ 2 < p ( λ − λ 1 ) ,$
we have $λ 1 + λ 2 = λ .$ For $λ 1 + λ 2 = λ$ $( 0 < λ 1 , λ 2 < λ ) ,$ we reduce (19) to the following:
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + m d x d y > B ( λ 1 + m , λ 2 ) × ∫ 0 ∞ x p ( 1 − λ 1 − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ 2 ) − 1 ( g ( m ) ( y ) ) q d y 1 q ,$
where the constant factor $B ( λ 1 + m , λ 2 )$ is the best possible.
Remark 5.
For $r > 1 , 1 r + 1 s = 1 , λ 1 = λ r , λ 2 = λ s$ in (25), we have the following reverse inequality
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) λ + n d x d y > ∏ i = 0 m − 1 ( λ r + i ) [ ∏ j = 0 n − 1 ( λ + j ) ] − 1 B ( λ r , λ s ) × ∫ 0 ∞ x p ( 1 − λ r − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q ( 1 − λ s ) − 1 ( g ( n ) ( y ) ) q d y 1 q ,$
where the constant factor
$∏ i = 0 m − 1 ( λ r + i ) [ ∏ j = 0 n − 1 ( λ + j ) ] − 1 B ( λ r , λ s )$
is the best possible. In particular, for $λ = 1 ,$ we have
$∫ 0 ∞ ∫ 0 ∞ f ( x ) g ( y ) ( x + y ) 1 + n d x d y > π n ! sin ( π r ) ∫ 0 ∞ x p ( 1 s − m ) − 1 F m p ( x ) d x 1 p ∫ 0 ∞ y q r − 1 ( g ( n ) ( y ) ) q d y 1 q ,$
where the constant factor $π n ! sin ( π r )$ is still the best possible.

## 5. Conclusions

In the present paper, we followed the methods of [15,17], used weight functions and introduced parameters in order to prove a new Hardy–Hilbert-type integral inequality with the kernel $1 ( x + y ) λ + n$ involving one multiple upper limit function and one derivative function of higher order. In this study, we also considered equivalent statements of the best possible constant factor related to the parameters and obtained some particular inequalities, in addition to considering the case of reverses. The lemmas and theorems presented in this work provide an extensive account of this type of inequalities.

## Author Contributions

Writing—original draft preparation, B.Y. and M.T.R.; writing—review and editing, B.Y. and M.T.R. Both authors contributed equally in the preparation of this work. All authors have read and agreed to the published version of the manuscript.

## Funding

This work was supported by the National Natural Science Foundation (No. 61772140), Science and Technology Projects in Guangzhou (No. 202103010004) and the Characteristic Innovation Project of Guangdong Provincial Colleges and Universities (No. 2020KTSCX088).

Not applicable.

Not applicable.

Not applicable.

## Acknowledgments

This work was supported by the National Natural Science Foundation (No. 61772140), Science and Technology Projects in Guangzhou (No. 202103010004) and the Characteristic Innovation Project of Guangdong Provincial Colleges and Universities (No. 2020KTSCX088). We are grateful for this support.

## Conflicts of Interest

The authors have no conflict of interests.

## References

1. Hardy, G.H.; Littlewood, J.E.; Polya, G. Inequalities; Cambridge University Press: Cambridge, UK, 1934. [Google Scholar]
2. Yang, B.C. The Norm of Operator and Hilbert-Type Inequalities; Science Press: Beijing, China, 2009. [Google Scholar]
3. Yang, B.C. Hilbert-Type Integral Inequalities; Bentham Science Publishers Ltd.: Sharjah, United Arab Emirates, 2009. [Google Scholar]
4. Yang, B.C. On the norm of an integral operator and applications. J. Math. Anal. Appl. 2006, 321, 182–192. [Google Scholar] [CrossRef]
5. Xu, J.S. Hardy-Hilbert’s inequalities with two parameters. Adv. Math. 2007, 36, 63–76. [Google Scholar]
6. Xie, Z.T.; Zeng, Z.; Sun, Y.F. A new Hilbert-type inequality with the homogeneous kernel of degree-2. Adv. Appl. Math. 2013, 12, 391–401. [Google Scholar]
7. Zeng, Z.; Raja Rama Gandhi, K.; Xie, Z.T. A new Hilbert-type inequality with the homogeneous kernel of degree-2 and with the integral. Bull. Math. Sci. Appl. 2014, 3, 11–20. [Google Scholar]
8. Xin, D.M. A Hilbert-type integral inequality with the homogeneous kernel of zero degree. Math. Theory Appl. 2010, 30, 70–74. [Google Scholar]
9. Azar, L.E. The connection between Hilbert and Hardy inequalities. J. Inequalities Appl. 2013, 2013, 452. [Google Scholar] [CrossRef]
10. Batbold, T.; Sawano, Y. Sharp bounds for m-linear Hilbert-type operators on the weighted Morrey spaces. Math. Inequalities Appl. 2017, 20, 263–283. [Google Scholar] [CrossRef]
11. Adiyasuren, V.; Batbold, T.; Krnic, M. Multiple Hilbert-type inequalities involving some differential operators. Banach J. Math. Anal. 2016, 10, 320–337. [Google Scholar] [CrossRef]
12. Adiyasuren, V.; Batbold, T.; Krni’c, M. Hilbert–type inequalities involving differential operators, the best constants and applications. Math. Inequalities Appl. 2015, 18, 111–124. [Google Scholar] [CrossRef]
13. Batbold, T.; Azar, L.E. A new form of Hilbert integral inequality. Math. Inequalities Appl. 2018, 12, 379–390. [Google Scholar] [CrossRef]
14. Krnic, M.; Pecaric, J. Extension of Hilbert’s inequality. J. Math. Anal. Appl. 2006, 324, 150–160. [Google Scholar] [CrossRef]
15. Adiyasuren, V.; Batbold, T.; Azar, L.E. A new discrete Hilbert-type inequality involving partial sums. J. Inequalities Appl. 2019, 2019, 127. [Google Scholar] [CrossRef]
16. Mo, H.M.; Yang, B.C. On a new Hilbert-type integral inequality involving the upper limit functions. J. Inequalities Appl. 2020, 2020, 5. [Google Scholar] [CrossRef]
17. Hong, Y.; Wen, Y. A necessary and sufficient condition of that Hilbert type series inequality with homogeneous kernel has the best constant factor. Ann. Math. 2016, 37, 329–336. [Google Scholar]
18. Hong, Y. On the structure character of Hilbert’s type integral inequality with homogeneous kernel and applications. J. Jilin Univ. 2017, 55, 189–194. [Google Scholar]
19. Xin, D.M.; Yang, B.C.; Wang, A.Z. Equivalent property of a Hilbert-type integral inequality related to the beta function in the whole plane. J. Funct. Spaces 2018, 2018, 2691816. [Google Scholar] [CrossRef]
20. Liao, J.Q.; Wu, S.H.; Yang, B.C. On a new half-discrete Hilbert-type inequality involving the variable upper limit integral and the partial sum. Mathematics 2020, 8, 229. [Google Scholar] [CrossRef]
21. He, B.; Hong, Y.; Li, Z. Conditions for the validity of a class of optimal Hilbert-type multiple integral inequalities with non-homogeneous. J. Inequalities Appl. 2021, 2021, 64. [Google Scholar] [CrossRef]
22. Chen, Q.; He, B.; Hong, Y.; Li, Z. Equivalent parameter conditions for the validity of half-discrete Hilbert-type multiple integral inequality with generalized homogeneous kernel. J. Funct. Spaces 2020, 2020, 7414861. [Google Scholar] [CrossRef]
23. He, B.; Hong, Y.; Chen, Q. The equivalent parameter conditions for constructing multiple integral half-discrete Hilbert-type inequalities with a class of non-homogeneous kernels and their applications. Open Math. 2021, 19, 400–411. [Google Scholar] [CrossRef]
24. Hong, Y.; Huang, Q.L.; Chen, Q. The parameter conditions for the existence of the Hilbert-type multiple integral inequality and its best constant factor. Ann. Funct. Anal. 2020, 12, 7. [Google Scholar] [CrossRef]
25. Hong, Y. Progress in the Study of Hilbert-Type Integral Inequalities from Homogeneous Kernels to Non-Homogeneous Kernels. J. Guangdong Univ. Educ. 2020. [Google Scholar]
26. Hong, Y.; Chen, Q.; Wu, C.Y. The best matching parameters for semi-discrete Hilbert-type inequality with quasi-homogeneous kernel. Math. Appl. 2021, 34, 779–785. [Google Scholar]
27. Hong, Y.; He, B. The optimal matching parameter of half-discrete Hilbert-type multiple integral inequalities with non-homogeneous kernels and applications. Chin. Q. J. Math. 2021, 36, 252–262. [Google Scholar]
28. Wang, Z.X.; Guo, D.R. Introduction to Special Functions; Science Press: Beijing, China, 1979. [Google Scholar]
29. Kuang, J.C. Applied Inequalities; Shangdong Science and Technology Press: Jinan, China, 2004. [Google Scholar]
30. Kuang, J.C. Real and Functional Analysis (Continuation); Higher Education Press: Beijing, China, 2015; Volume 2. [Google Scholar]
 Disclaimer/Publisher’s Note: The statements, opinions and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s). MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions or products referred to in the content.

## Share and Cite

MDPI and ACS Style

Yang, B.; Rassias, M.T. A New Hardy–Hilbert-Type Integral Inequality Involving One Multiple Upper Limit Function and One Derivative Function of Higher Order. Axioms 2023, 12, 499. https://doi.org/10.3390/axioms12050499

AMA Style

Yang B, Rassias MT. A New Hardy–Hilbert-Type Integral Inequality Involving One Multiple Upper Limit Function and One Derivative Function of Higher Order. Axioms. 2023; 12(5):499. https://doi.org/10.3390/axioms12050499

Chicago/Turabian Style

Yang, Bicheng, and Michael Th. Rassias. 2023. "A New Hardy–Hilbert-Type Integral Inequality Involving One Multiple Upper Limit Function and One Derivative Function of Higher Order" Axioms 12, no. 5: 499. https://doi.org/10.3390/axioms12050499

Note that from the first issue of 2016, this journal uses article numbers instead of page numbers. See further details here.